Internal determinants of share price movements among listed companies in Nigeria: does gender diversity in boardroom matter? - Edirin, Jeroh (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study focused on ascertaining the value relevance of gender diversity in determining share price movements among listed firms by obtaining evidence from a notable Sub-Saharan African (SSA) country - Nigeria. Panel data were collated from companies’ annual reports for 6 years covering 2012 – 2017. In estimating the models formulated to test the postulated hypotheses, the multiple regression technique was applied along with the fixed and random effect analyses. On a general note, findings indicate that the level of gender diversity in corporate boards are value relevant in determining movements in share prices since they have strong and positive effect on variations in share prices of listed firms. We therefore recommend amongst others, the passage and enforcement of legislations by the relevant and appropriate authorities and organs of regulatory controls in Nigeria, requiring all corporate boards to have a minimum proportion of female presence in their respective boardrooms. Overall, the outcome of this study contributes to existing body of empirical knowledge on the statistical link between movements in the prices of companies’ stocks and boardroom gender diversity.